وسائل الإبانة البلاغية في مباحث المعتزلة - دراسة تطبيقية على الكشاف للزمخشري - عثماني, اسراء; بوضبية, اميرة; ذيب, ايمان (جامعة الوادي - University of Eloued, 2023)
الملخص: يتناول موضوع المذكرة هذا: وسائل الإبانة البلاغية عند المعتزلة دراسة تطبيقية في تفسير الكشاف للزمخشري والذي نحاول فيه الإجابة على الإشكال التالي: ما هي وسائل الإبانة البلاغية عند المعتزلة؟ لذلك يتناول هذا البحث وسائل الإبانة التي طبقها الزمخشري في كتابه الكشاف وذلك لبيان موضع إعجاز القرآن الكريم ومنه اشتملت خطة بحثنا على مقدمة وفصلين وخاتمة, أما الفصل الأول فكان الحديث عن وسائل الإبانة البلاغية أما الثاني دراسة تطبيقية في تفسير الكشاف للزمخشري حول وسائل الإبانة ومنه توصلنا إلى عدة نتائج أهمها: أن الزمخشري عمل على تطبيق وسائل الإبانة في كتابه الكشاف حيث بين من خلاله ما تؤديه عملية الإبانة عن المعنى. The subject of this memorandum deals with: The means of rhetorical expression of the Mu'tazila An applied study in the interpretation of Al-Kashshaf of Zamakhshari, in which we try to answer the following problem: What are the means of rhetorical expression of the Mu'tazila? Therefore, this research deals with the means of expression that Al-Zamakhshari applied in his book Al-Kashshaf, in order to clarify the position of the miraculousness of the Holy Qur’an, and from it, our research plan included an introduction, two chapters, and a conclusion. Several results, the most important of which are: that Al-Zamakhshari worked on the application of the means of expression in his book Al-Kashf, where he clarified through it what the process of expression of meaning performs.
Keywords: rhetoric, Mu'tazilah, eloquence, Zamakhshari.; عربيّــة: البلاغة، المعتزلة، الابانة، الزمخشري.